Modified REACH Counseling Model to Increase Forgiveness Motivation in Marital Relationship Distress - Sandjaja, Stefanus Soejanto (Gadjah Mada Journal of Professional Psychology (GamaJPP), 2026)
Interpersonal conflict, verbal abuse in the household, and demands to behave like someone else significantly impact an individual’s psychological functioning and trigger marital relationship distress. The aim of this study was to evaluate the role of the modified REACH counseling model in increasing forgiveness motivation in a 33-year-old woman experiencing relationship distress with her spouse. The research used a one-case pretest-posttest design and data collection was conducted using the Indonesian Transgression-Related Interpersonal Motivation Scale (The Indonesian TRIM-18). The findings showed a reduction in the dimensions of avoidance motivation and revenge motivation, decreasing from high to low categories. Likewise, the benevolence motivation dimension improved positively, from low to moderate. Qualitative data also supported the quantitative findings. These outcomes proved that the application of the modified REACH counseling model can deliver positive changes in the context of a high-conflict marital relationship, which is further discussed in the article along with implications and recommendations.